2020
DOI: 10.1016/j.omtn.2019.10.036
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Kcnq1ot1/miR-381-3p/ETS2 Axis Regulates Inflammation in Mouse Models of Acute Respiratory Distress Syndrome

Abstract: Inflammatory mediators play a key role in the pathogenesis of acute respiratory distress syndrome (ARDS). In this study, we aimed to explore the involvement of the Kcnq1 opposite strand/antisense transcript 1 (Kcnq1ot1)/miR-381-3p/E26 transformation-specific proto-oncogene 2 (ETS2) axis in inflammation of lipopolysaccharide (LPS)-induced ARDS. Microarray analysis revealed ETS2 as an upregulated gene in ARDS. Then, a LPS-induced ARDS mouse model was constructed, with a series of gain- or loss-of-function experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…L2880; Sigma-Aldrich, St. Louis, MO, USA). 18,19 The NC group was injected with the same amount of saline. The two groups were further divided into subgroups of 2, 6, 12, and 24 hours with six rats for each time point.…”
Section: Ali Modeling and Groupingmentioning
confidence: 99%
“…L2880; Sigma-Aldrich, St. Louis, MO, USA). 18,19 The NC group was injected with the same amount of saline. The two groups were further divided into subgroups of 2, 6, 12, and 24 hours with six rats for each time point.…”
Section: Ali Modeling and Groupingmentioning
confidence: 99%
“…Because the molecular mechanism is complex in cell processes, the effect of SNHG15 may be influenced by other regulatory factors, especially for the adverse changes. Numerous studies have been revealed that miRNAs serve as suppressors in the levels of inflammatory factors of multiple diseases [ 35–38 ], including in DN in vitro [ 20–22 ]. Zha et al have demonstrated that the decreased expression of miR-181a dramatically elevates the levels of inflammatory factors in HG-treated RAW264.7 cells, while the expression of inflammatory factors is inhibited by miR-181a overexpression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been revealed that miRNAs serve as suppressors in the levels of inflammatory factors of multiple diseases [35][36][37][38], including in DN in vitro [20][21][22]. ICAM-1 has been confirmed to distinctly up-regulate in DN in vitro [42][43][44][45].…”
Section: Snhg15 Knockdown Promotes the Viability And Inhibits Inflammatory Response Of Hg-induced Hgmcs By Regulating Mir-141/icam-1mentioning
confidence: 99%
“…The tumor suppressor role of miR-381-3p has been demonstrated, including inhibiting cell proliferation, metastasis, and facilitating cell cycle arrest and apoptosis [ 16 , 18 ]. In addition, miR-381-3p had a connection with inflammatory responses in mouse models of spinal cord injury and acute respiratory distress syndrome [ 28 , 29 ]. In NSCLC, miR-381-3p was sponged by circFGFR1, an oncogenic circRNA functioning in proliferation, metastasis, and immune evasion capacities of tumor cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%